Novel manufacturing method for highly flexible poly(lactic acid) foams and ferroelectrets - Dániel Vadas; Katalin Bocz; Tamás Igricz; János Volk; Sándor Bordács; Lajos Madarász; György Marosi (Advanced Industrial and Engineering Polymer Research, 2024)
Poly (lactic acid) (PLA) foams have demonstrated a high variety of functional characteristics, still, the rigidity of this cellular material remains a major limiting factor when it comes to implementation options. In this contribution, PLA foams with outstanding flexibility were created for the first time by a new approach of uniaxial stretching and immediate relaxation following supercritical CO2-assisted extrusion foaming. Instead of improving the resilience of the PLA raw material, structural elasticity of the foam was achieved via altering the deformation mechanism from cell wall collapse or rupture towards reversible and extensive flexural strain. In addition, PLA foams with excellent piezoelectric properties were also achieved via high-voltage corona poling, giving additional function to the lens-like anisotropic foam cells. This foaming technology creates the opportunity to produce PLA piezoelectrets in a way entirely different from the state-of-the-art methods. Correlation between the tensile as well as compression elongations and moduli, cell morphology and longitudinal piezoelectric coefficients (d33) of electretized foam samples were studied. Unprecedented reversible tensile elongations of up to 16% and total elongations of up to 35% were reached, as well as considerable d33 values in the range of 50–320 pC/N were obtained for PLA ferroelectrets.